Mortality among people living with HIV/AIDS with non-small-cell lung cancer in the modern HAART Era. Issue 7 (3rd July 2018) - Smith, Danielle M.; Salters, Kate A.; Eyawo, Oghenowede; Franco-Villalobos, Conrado; Jabbari, Shahab; Wiseman, Sam M.; Press, Natasha; Montaner, Julio S.G.; Man, S. F. Paul; Hull, Mark; Hogg, Robert S.
ABSTRACT: People living with HIV (PLWHA) with adequate access to modern combination antiretroviral therapy (cART) are living longer and experiencing reduced AIDS-related morbidity and mortality. However, increases in non-AIDS related conditions, such as certain cancers, have accompanied these therapeutic advances over time. As such, our study objective was to determine the impact of HIV on all-cause and lung cancer-specific mortality amongst PLWHA with diagnoses of non-small-cell lung cancer (NSCLC) and HIV-negative individuals with NSCLC. This analysis was inclusive of PLWHA on and off cART over the age of 19 years and a 10% comparison sample from the BC population ≥19 years, over a 13-year period (2000–2013). Kaplan-Meier estimates, Cox PH models, and competing risk analysis for all-cause and cause-specific mortality (respectively) compared PLWHA to HIV-negative individuals, controlling for age, gender, cancer stage, co-morbidities; and nadir CD4 count, viral load, and injection drug use for a HIV-positive specific analysis. We identified 71 PLWHA and 2463 HIV-negative individuals diagnosed with NSCLC between 2000 and 2013. PLWHA with NSCLC were diagnosed at a significantly younger age than HIV-negative individuals (median age 57 vs 71 years, p  < 0.01). We found no significant difference in lung cancer-specific mortality. However, in multivariate analysis, HIV was associated with greater all-cause mortality (adjusted hazard ratio [aHR]:1.44; 95% confidence interval [CI]: 1.08–1.90), with median survival of 4 months for PLWHA, and 10 months for HIV-negative. Higher nadir CD4 count was protective against mortality (aHR: 0.33, 95% CI: 0.17–0.64) amongst PLWHA in multivariate analysis. Our analysis suggests that PLWHA in the modern cART era experience similar lung cancer survival outcomes compared to the general BC population with NSCLC. However, we also observed significantly higher all-cause mortality among PLWHA with NSCLC, which may warrant further inquiry into the role of HIV in exacerbating mortality among PLWHA with comorbidities and cancer.